EVALUATION OF PAPAYA RINGSPOT VIRUS AS A VECTOR FOR EXPRESSION OF DENGUE E PROTEIN DOMAIN III IN CUCURBITA PEPO (ZUCCHINI) PLANTS - S. Libsittikul; S. Khongwichit; D. R. Smith; Y-K. Yap (Journal of Animal and Plant Sciences, 2015)
Dengue fever is the most significant mosquito transmitted viral disease worldwide, but there is no commercially available vaccine to protect against infection.  Subunit vaccines, comprising of a small antigenic region of the dengue E protein offer considerable advantages over more traditional methodologies of vaccine production, but are hampered by the requirement to produce large quantities of purified protein free from any potential pathogen or toxic agent.  This study sought to determine whether Papaya ringspot virus (PRSV; Family Potyviridae, Genus Potyvirus, Species Papaya ringspot virus) could be engineered to accommodate the expression of a heterologous protein, specifically domain III of the DENV 2 E protein (D2EDIII), a promising subunit vaccine candidate.  An infectious clone expressing DENV 2 E protein domain III was successfully constructed, and the insert showed stability over two passages in Cucurbita pepo (zucchini) plants.  While the construct was designed to generate a discrete antigen moiety (D2EDIII) after proteolytic processing, results showed that the E protein insert was fused to the PRSV P1 protein, suggesting inefficient protease processing at the P1/ D2EDIII junction.  The proof of principle results however confirm that PRSV could be used as an expression vector for heterologous protein expression in plants.
Keywords: dengue; papaya ringspot virus; sub-unit vaccine; zucchini